Politeness Strategies in Internalizing moderation Value used By Teacher of Arabic Language - Qomariyah, Lailatul; Setyabudi, Mohammad Arif (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The politeness strategy is the communication strategy used by the teacher by submitting to the politeness principle in his directive act. This is the teacher's effort to manage the class and internalize the value of moderation by accommodating mediocrity values, meaning tolerance, balance value in teaching Arabic to reach interactive and communicative education useful to improve students' personality as an effect of online learning for a long time. The purpose of this research is to analize the teacher's politeness strategy by internalizing the value of moderation in Dar Al-Salam islamic boarding school. this research was designed with a qualitative approach, with the type of case study. A method for collecting data by making observations in teaching Arabic, and documenting the teacher's politeness strategy in her guiding actions, and interviewing the context of these teacher’s acts. The results of this research are, the politeness strategy used by the teacher in his speech acts in two ways: 1) the direct politeness strategy with four functions, a) the request, b) the command, c) the invitation, d) the prohibition, and 2) the indirect politeness strategy with two functions, a) the request and b) the prohibition. The results of this research contribute to the teacher's strategy in classroom management by using several politeness strategies in speech act’s so that learning is more interactive and communicative due to mutual respect and tolerance between teacher and students.Therefore, it is necessary to conduct the following research on understanding the values of moderation through the curriculum in teaching Arabic